Development of Theory of Planned Behavior (TPB) With Self-Efficacy to Explain The Intention To Be A Farmer in The Zinenial Generation - Widagda K, I Gusti Ngurah Jaya Agung; Yasa, Ni Nyoman Kerti; Rahmayanti, Putu Laksmita Dewi; Tirtayani, I Gusti Ayu; Dharmanegara, Ida Bagus Agung (School of Business, Bogor Agricultural University (SB-IPB), 2022)
The purpose of this study was to develop a theory of planned behavior (TPB) that explains the intentions of Generation Z farmers using self-efficacy variables. The population of this study is Gen Z from Bali. The sample size used was 210 with the planned sampling method. The analysis technique used is path analysis by SEM-PLS. Results showed that attitudes did not affect willingness to farm. Subjective norms and PBC had a positive and significant effect on intention to become a farmer, attitudes, and self-efficacy between subjective norms and PBC. and it made a big impression. , and self-efficacy can act as mediators of attitudes, subjective norms, and the impact PBC has on their intent to become a Gen Z farmer in Bali. It is therefore important that government, educational institutions and parents understand that farming is a good career, the more self-efficacy a person has towards farming, the easier it is for someone to get into it Enter Farming Farmer So You Can Encouraged Gen Z have big intentions to become farmers. Likewise, the availability of land and farming skills must find a solution so that they continue to improve in order to increase the intention to become a farmer in the Z generation. Keywords: attitude, subjective norm, PBC, self-efficacy, intention to become a farmer